EFFECTIVENESS OF ORAL PROPRANOLOL VERSUS TOPICAL TIMOLOL IN THE TREATMENT OF INFANTILE HEMANGIOMA – A CASE-CONTROL STUDY. - Guru, Kranti Swagatika; Meher, Sanjib Kumar; Behera, Saujanya (Student's Journal of Health Research Africa, 2025)
Background Infantile hemangiomas (IH) are the most common vascular tumors in infancy, with oral propranolol established as an effective treatment in 2008. However, due to systemic side effects, topical timolol has emerged as an alternative, necessitating a comparison of its efficacy and safety. This study aims to evaluate and contrast the effectiveness of oral propranolol versus topical timolol in treating infantile haemangiomas, focusing on their respective efficacy, safety profiles, and clinical outcomes. Methods A prospective review was conducted at VSSIMSAR, Burla, over two years (January 2023 to January 2025), involving 104 children (3 months–4 years) with superficial infantile hemangiomas. Patients were randomized into two groups receiving either oral propranolol (1.5- 2 mg/kg daily) or topical timolol maleate (0.5% twice daily) for up to six months. Treatment response was assessed through lesion size reduction and classified using Achauer’s four-point scale. Results Both propranolol (95%) and timolol (93.4%) demonstrated high efficacy, with propranolol showing a faster response. At one month, 10 children in the propranolol group showed a significant reduction versus 5 in the timolol group. By six months, 45 and 42 children achieved marked improvement, respectively. Propranolol was associated with mild systemic side effects, while timolol was well-tolerated. Conclusion Both propranolol and timolol effectively treated infantile hemangiomas, with propranolol acting faster but with mild systemic effects. Early intervention is crucial for optimal outcomes. Recommendation Topical timolol is recommended as a safe and effective first-line treatment for superficial infantile hemangiomas, especially in cases where systemic side effects are a concern.